MATHEMATICS HOMEWORK: IS IT STILL NECESSARY? - Aprian Subhananto; Wafiq Nurul Huda; Malik Ibrahim; Rita Wahyuni (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
In recent years, it has been debated whether homework for mathematics subjects is still necessary or not. Mathematics is a science that requires a lot of practice and repetition so that the material communicated can be mastered by students perfectly so it requires practice in the form of homework with clear, useful goals and stimulating creativity and collaboration in order to be able to do it. However, on the other hand, homework in mathematics will reduce quality time at home, especially if homework simply moves activities from school to home. We know that mathematics is a very difficult subject and everyone avoids interacting and communicating with mathematics. This article was written using the library research method. Library materials were searched using the Google Search Engine for scientific literature. The data collected relates to homework carried out by elementary school students. Data analysis uses Huberman's model which includes data reduction, data display and data verification stages. The results obtained are how to search for literature reviews, namely using Google Scholar. The search words used were Homework, Mathematics Homework, . There are 2 things that can be done to support homework activities in elementary schools, namely assignment methods according to student characteristics, and parental guidance. The assignment method can be used by teachers to train students' learning at home. Parental guidance can be done to bring feelings and goodness closer to the family.